No‐tillage increased corn yields and carbon sequestration. (10th September 2020) - Chen, Tianyu; Zhang, Yifei; Fu, Jian; Yang, Li; Chi, Yuxin; Wu, Peng; Yin, Xuewei; Wang, Huaipeng; Yang, Kejun; Wang, Yufeng
Abstract: Changes in agricultural management can potentially change the rate of C sequestration. The rain‐fed agricultural areas of the Songnen Plain are China's main grain‐producing areas, and this region has a temperate monsoon climate with an annual average temperature of 2.0−5.6 °C, annual average rainfall of 350−460 mm, and annual evaporation of 1, 000−1, 600 mm. In a short‐term experiment (2014−2019), the effects of no‐tillage (NT), no‐tillage and subsoiling (NTS), rotary and ridge tillage (RT), rotary and ridge tillage and subsoiling (RTS), rotary and flatten tillage (FT), and rotary and flatten tillage and subsoiling (FTS) on alkaline meadow soil in the surface 0−30 cm of soil was investigated. Measurements after 5 yr showed that, under NT at 0‐ to 30‐cm depth, the bulk density of soil, soil water content, and soil nutrient content significantly increased when compared with RT and FT. Soil organic carbon (SOC) stocks at 0−30 cm were increased by 2.23% (0.99 Mg ha −1 ) under NT, and the annual accumulation rate of SOC stocks under NT reached 0.20 Mg ha −1 . Under RT and FT, SOC stocks decreased by 2.11% (0.94 Mg ha −1 ) and 2.18% (0.97 Mg ha −1 ), respectively, when compared with the beginning of the experiment. This indicates that NT, compared with RT and FT, reduces soil C loss and is conducive to the C sequestration.